FORMS, METHODS AND MEANS OF DEVELOPING MECHANISMS FOR IMPLEMENTING THE EDUCATIONAL PROCESS IN MILITARY TRAINING EDUCATIONAL UNITS - Zarifboy Jabbarov (Web of Journals Publishing, 2023)
The article discusses the problems of developing mechanisms for organizing and implementing the educational process in military educational units of State higher educational institutions. The presence of a high level of military professional orientation, education and professional motivation ensures good adaptation, military professional development and the realization of the psychological resources of the future military specialist. In addition, the article briefly examines the theoretical views of scientists on the development of the educational process.
Keywords: military-professional, military specialist, psychologist resources, cognitive motives, civil competence of officers, professional motivation.